Perancangan Sistem Informasi Retensi Rekam Medis Pasien Rawat Inap Menggunakan Visual Studio 2010 di Rumah Sakit Jasa Kartini Tasikmalaya - Resa Yusnia; Sali Setiatin; Widya Nadiroh; Candra Mecca Sufyana (Jurnal Health Sains, 2021)
The hospital is a place to organize health efforts, namely every activity to maintain and improve health and aims to realize optimal levels of health for the community. This study aims to design an information system for inpatient medical record retention using Microsoft Visual Studio 2010 at the Jasa Kartini Hospital, Tasikmalaya. The research method used is a qualitative method with a descriptive approach. Data collection techniques are using observation, interviews and literature studies related to the subject matter of the research. As for the software development method using the waterfall. Based on the research conducted, various problems were found, including the medical record files that had been retained were not well organized at the time of storage so that they were not sequentially according to the medical record number, the lack of storage racks so that the medical records were not well organized and the retention process was slow. Therefore, it is necessary to design a medical record retention information system in the form of an application. The system design method uses Flowmap, DFD (Data Flow Diagram) and ERD (Entity Relation Diagram) and is implemented with Microsoft Visual Studio 2010 programming language with Microsoft Access database. Testing is done using the black box with the results of each successful form according to the design procedure.